News blogs versus mainstream media: Measuring the gap through a frame analysis of Greek blogs. (October 2017) - Touri, Maria; Kostarella, Ioanna
This article offers an empirical examination of the power of independent news blogs to expand the boundaries of public debates, through their capacity not only to host volumes of information but also to frame it in unique packages. Despite the scholarly attention given to blogs as a counterforce to traditional news media, there are unanswered questions regarding the discrepancy in the qualitative characteristics of the debates promoted by these two realms. We aim to offer an empirical test of this potential gap with an innovative content analysis that draws on framing research and corpus linguistic techniques. This is performed in the context of Greece, where a rapid increase in the volume of blogging has created a new platform for political debate. Through a computer-assisted qualitative frame analysis of partisan newspapers and independent news blogs, we find differences in the breadth of certain frames that could prove significant for audiences' understanding of current affairs.